On a class of nonlinear obstacle problems with nonstandard growth. (10th September 2014) - Zou, Weilin; Wang, Wei; Bi, Yanhui
<x xml:space="preserve">Abstract</x> In this paper, we study a class of nonlinear obstacle problems with nonstandard growth. We obtain the L∞ estimate on the solutions and prove the existence and uniqueness of solutions to such problems. Our results are generalizations of the corresponding results in the constant exponent case. Copyright © 2014 John Wiley & Sons, Ltd.